2016
DOI: 10.1007/s00038-016-0845-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of network characteristics on substance use outcomes among homeless former foster youth

Abstract: Results highlight the need for a more in-depth understanding of the impact of network changes over time and their effect on substance use outcomes in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Using this method, distinct social support network typologies and composition were found among this sample of youth experiencing homelessness. Consistent with prior research (Barman‐Adhikari et al, ; Ennett et al, ; Yoshioka‐Maxwell & Rice, ), youth experiencing homelessness were predominantly characterised by low or no social supports. For youth with a social support network, the networks were small and primarily comprised of peers, followed by family and staff.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Using this method, distinct social support network typologies and composition were found among this sample of youth experiencing homelessness. Consistent with prior research (Barman‐Adhikari et al, ; Ennett et al, ; Yoshioka‐Maxwell & Rice, ), youth experiencing homelessness were predominantly characterised by low or no social supports. For youth with a social support network, the networks were small and primarily comprised of peers, followed by family and staff.…”
Section: Discussionsupporting
confidence: 85%
“…A somewhat surprising finding is that former foster youth experiencing homelessness had greater odds of being characterised by the high staff emotional and service support class when compared to the low or no support class. Although prior research suggests that former foster youth experiencing homelessness report significantly fewer people in their networks than youth without a history of foster care (Negriff, James, & Trickett, ; Yoshioka‐Maxwell & Rice, ), it is possible that a subgroup of youth remain connected to past caseworkers or involved with other service systems. Additionally, youth who have been connected to the child welfare system may have learned how to navigate the web of social services and supports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although time spent in foster care and age at exit from foster care may initially appear to be contradictory, these findings indicate that shorter placements in out-of-home care starting at an older age may protect against some HIV-risk behaviors, compared to a longer time spent in care starting at an earlier age. As other studies have found, these results may relate to the types of social network connections made during youth's time spent in foster care [38]. Finally, the timing of homelessness experiences provides some insight into risk factors for this population, with rates of both drug use with sex and engagement in exchange sex increased among youth who experience homelessness before they exit foster care.…”
Section: Discussionmentioning
confidence: 60%
“…When social networks are comprised largely of other youth exhibiting deviant behaviors, the risks associated with living on the streets are magnified for individuals operating within those networks (McMorris, Tyler, Whitbeck, & Hoyt, 2002;Rice, Milburn, & Monro, 2011). Negative peer influences in the street-based networks of youth experiencing homelessness span a wide spectrum of risk-taking behaviors, including violence (Petering, Rice, & Rhoades, 2016), mental health (Fulginiti, Rice, Hsu, Rhoades, & Winetrobe, 2016), substance use (Barman-Adhikari, Rice, Winetrobe, & Petering, 2015;Yoshioka-Maxwell & Rice, 2017), and sexual risk-taking (Barman-Adhikari, Hsu, Begun, Portillo, & Rice, 2017).…”
Section: Peers and Sexual Health Among Youth Experiencing Homelessnessmentioning
confidence: 99%